Impacts on G.C.E Ordinary Level Results Among Bilingual Students and Tamil Medium Students ( A Comparative Based Research) - M.J. Fathima Sabrinas; M.J.F Sujani; MB Nowzath; MR. Rishad Muhammed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research was carried out with the aim of identifying the impact of bilingual education by comparing the O/L results among the G.C.E O/L Tamil medium and bilingual students at KM/STR/AL-Marjan Muslim Ladies College, Sammanthurai. Writing, listening, and speaking skills are most important part in English which mainly committed by L2 learners. The examination department measures those students’ lower performance in their exam. The Standard English has been going very low nowadays among L2 learners. But this problem is less in bilingual or L1 learners cause that the impact of bilingual and medium education and instruction. This is the reason researcher made the investigation about it. This research contacted among 2015 O/L batch students at KM/STR/Al-Marjan Muslim Ladies College Sammanthurai. The participants in this research were 26 students those were coming from bilingual and Tamil medium. The study technique of quantitative approach used. The data we're collected from using test strategies of pre-test,